THE ABILITY OF BREADFRUIT STARCH NANOPARTICLE-STABILIZED PICKERING EMULSION FOR ENCAPSULATING CINNAMON ESSENTIAL OIL - HARSANTO, BOVI WIRA; SUPRIYANTO; KARTINI, IINDRIANA; PRANOTO, YUDI (Malaysian Applied Biology, 2022)
Cinnamon essential oil (CO) is susceptible to decreased stability during storage, limiting its application in food products. Pickering emulsion stabilized by starch nanoparticles becomes a potential encapsulating method that can improve CO stability. This study aimed to investigate the ability of breadfruit starch nanoparticles-stabilized Pickering emulsion to encapsulate CO with various concentrations. Encapsulation process was carried out using the high-energy emulsification method with dispersing CO (0.05%; 0.1%; 0.5%; 1% w/w) in emulsion. The loading efficiency of CO and emulsion properties were evaluated. Retention of CO was also observed in 7 days-storage. Results showed that 0.5% and 1% CO were encapsulated effectively and stable in Pickering emulsion, with loading efficiency and CO retention ranging from 79.49-81.13% and 78.86-79.20%, respectively. The addition of 0.5% and 1% CO increased yellowness (+a*: 7.45-8.99) as well as decreased whiteness (+L*: 85.77-86.06) and viscosity (629.9-721.8 cP) of Pickering emulsion. However, differences in CO concentrations did not affect the emulsion index of Pickering emulsion. These findings concluded that breadfruit starch nanoparticles-stabilized Pickering emulsion could encapsulate up to 0.5% and 1% CO with the best properties among other treatments. Therefore, breadfruit starch nanoparticles-stabilized Pickering emulsion can be an alternative as encapsulation method, which can later expand the application of CO in food products.